Comparison of Analgesic Effect of Valeriana officinalis and Mefenamic Acid on Primary Dysmenorrhea - A Kazemian; N Parvin; M Delaram; F Deris (Institue of Medicinal Plants, ACECR, 2017)
Background: Primary dysmenorrhea is a common and frequently disabling condition among women in adolescence and reproductive age. Based on results of large epidemiological studies, it is estimated that over a half of the population of young women suffers from dysmenorrhea. Some people are now seeking alternatives to conventional medicine such as herbal drugs. Objective: This study was designed to compare the analgesic effect of Valeriana officinalis with Mefenamic acid in treatment of primary dysmenorrhea. Methods: A randomized, controlled trial was undertaken among 39 female aged 16 to 42 who suffered from primary dysmenorrhea referred to gynecology clinic in Hajar hospital, Shahrekord, Iran.  The participants were randomly divided into two groups: Valeriana officinalis (n=18) and Mefenamicacid (n=21). In intervention group, the patients took350mg  Valerian three times a day, and in mefenamic group, the patients took 250 mg Mefenamic three times a day for three days(for three cycles), starting from the onset of bleeding or pain. Participants were followed for three cycles. Main outcome measures was the mean of pain severity at 3 months which recorded by Visual Analogue Scale. Results: There were no significant differences in age, menstural duration, menstural interval, and pain severity score at the beginning of the study in two groups (P>0.05). After the intervention, findings of the study revealed statistically significant reductions in mean of pain score in Valeriana officinalis (P<0.001) and Mefenamic acid (P<0.001) groups, but this reduction had not significant differences between two groups (P>0.05). Conclusion: Results shows that valerian has positive effect on treatment of primery dysmenorrheal. More clinical trials are needed to establish the efficacy of Valeriana officinalis in primary dysmenorrhea.